Transgender phenomenon in Serbia in the 21st century – knowledge of health providers on gender affirmation process - Vidić, Jelena (Engrami, 2020)
Introduction. In the past ten years significant changes have happened in the conceptualization and treatment of the transgender phenomenon. The treatment has been individualized and more grounded in the model of informed consent, more referrals to the gender clinics and gender teams have been recorded, and the ICD-11 finally removed gender dysphoria from the chapter on mental disorders to a separate chapter on sexual health. Objective. Having in mind these changes and the preparation for the upcoming implementation of ICD-11, we can expect more transgender patients in primary, secondary and tertiary health care. Therefore we conducted this research aiming to assess the level of knowledge and experiences of health providers on working with transgender patients. Method of work. We used a qualitative methodology and an online survey created for this research. The sample is convenient. Results. The final sample consists of 65 health providers. Data indicates a relatively low level of knowledge on different aspects of the gender reassignment process, but also a high level of interest in additional professional training in this area. Conclusion. Data indicates the need for additional training of health providers on working with transgender people during regular medical education and additional professional training. Our data can be used as a basis for creating training in this area and for future research. Key words: transgender, health providers, gender reassignment; depsychopathologization